The Effectiveness Of Content Marketing In Building Long-Term Customer Relationships - Utami Puji Lestari; Astrid Octavia Bahari; Klemens Mere (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
In today’s digital economy, content marketing has become a pivotal strategy for fostering sustainable customer relationships. Unlike traditional marketing approaches that emphasize short-term sales, content marketing focuses on delivering value through informative, engaging, and consistent content. Since 2020, research has highlighted how content marketing enhances trust, brand loyalty, and customer engagement by aligning messages with consumer needs and preferences. This literature review examines the effectiveness of content marketing in cultivating long-term relationships, exploring its role in customer retention, brand advocacy, and emotional connection with audiences. Evidence suggests that firms investing in high-quality, personalized content experience stronger customer loyalty and higher lifetime value compared to those relying solely on transactional marketing. However, challenges such as content saturation, authenticity, and measurement of long-term impact remain pressing concerns. By synthesizing recent findings, this study provides insights into how content marketing can be optimized to sustain meaningful customer relationships in the evolving digital landscape.